O ENSINO-APRENDIZAGEM DE LÍNGUA INGLESA EM ESCOLAS PÚBLICAS: O REAL E O IDEAL - Santos David, Ricardo (LINKSCIENCEPLACE, 2016)
One perceives that the education of the English in public, this loaded of currently critical schools and questionings. Ahead of this, the proposal of this article is to analyze the factors that make with that this language is so excellent in the modern world, and because before such increase it in such a way takes advantage an environment of difficulties and barriers of the part of the teacher as of the pupil in the brazilian public schools. From the traced referencial it is possible to say that the questions that hinder the idealize English it in the public schools happen of the difficulties of the professors in transmitting its knowledge and of the pupils of the lack of phonologic previous knowledge and of inherent problems to so well characterized public education in Brazil.